Optimize Banana Production through Innovative Growing System - T.P.Wijewardena; K.A.D.C. Kaluarachchi; V.S.V. Vitharana; W.M.S.D. Wijayasundara; Udara Srimath S. Samaratunge Arachchillage; Thilini Jayalath (International Journal of Engineering and Management Research, 2023)
Optimizing banana production through innovative systems is essential for sustainable cultivation. This research primarily focuses on banana variety identification using images and Convolutional Neural Networks (CNNs), detection of leaf diseases in banana trees through a machine learning approach, analysis and recommendation of optimal cultivation practices derived from interactions with farmers and external supervisors, and the generation of unique product ideas using differentiation strategies based on market research, consumer preferences, and insights from industry experts. Collectively, this study aims to revolutionize banana cultivation and marketing by amalgamating traditional farming insights with modern technological tools.